Highly efficient Co centers functionalized by nitrogen-doped carbon for the chemical fixation of CO2. Issue 69 (23rd November 2020) - Yang, Yuying; Li, Hong; Pei, Supeng; Liu, Feng; Feng, Wei; Zhang, Yongming
Abstract : A highly efficient Co@N x C functionalized heterocatalyst has been prepared to activate CO2 molecules and convert it into cyclic carbonates. Abstract : CO2, the main greenhouse gas, has received considerable attention due to environmental issues. From a scientific perspective, CO2 as a cheap and abundant carbon source, could be applied in synthesizing more valuable chemicals such as urea, formic acid, and cyclic carbonates. However, the high bond energy of CO (750 kJ mol −1 ) and the non-polarity property make CO2 molecules difficult to activate. In this paper, we have carefully designed a low-cost, stable and, most importantly, highly efficient Co-based heterocatalyst Co@N x C functionalized by nitrogen-doped carbon to activate CO2 molecules and convert it into cyclic carbonates. The CO2 conversion process could be triggered at very mild conditions (60 °C and 1 bar CO2 ). We carefully adjusted the nitrogen content in the carbon support to enhance the catalytic performance of Co centers via the interface effect. Consequently, the optimal catalyst displayed extraordinary activity toward the cycloaddition of CO2 with styrene oxide as high conversion (92%) and selectivity (>99%) were achieved in 4 h without byproducts.